The legal status and monastic organization on Mount Athos in the 18th century - Đukić Dalibor (Anali Pravnog Fakulteta u Beogradu)
Mount Athos represents a unique monastic community modelled after the great monastic centres of the Byzantine (Roman) Empire. Owing to the benevolence of Byzantine rulers a specific system of administration was established on Mount Athos, and the monks retained a high degree of self-administration. Although the Ottoman Empire in the 15th century took control of Mount Athos, its specific legal regime was not abolished. In the first centuries of Ottoman rule there were no significant attempts of introducing new or revising the old rules which regulated the organization of the administration on Mount Athos. It was only in the 18th century that the period of the more lively legislative activities began. During that period the Athonite administrative bodies, more or less similar to the current ones, were formed. This paper deals with the reasons that led to their creation and their evolution in the 18th century.